Renovascular Safety of Sunitinib in Renal Cell Carcinoma: The Prognostic Value of Hypertension and Proteinuria. Issue 3 (November 2017) - Launay-Vacher, Vincent; Ray-Coquard, Isabelle; Goldwasser, François; Mir, Olivier; Scotté, Florian; Spano, Jean-Philippe; Thery, Jean-Christophe; Beuzeboc, Philippe; Daniel, Catherine; Rey, Jean-Baptiste; Jouannaud, Christelle; Gligorov, Joseph; et al.
Background: The potential prognostic value of hypertension and proteinuria of anti- vascular endothelial growth factor (VEGF) drugs has not been assessed in routine clinical practice so far in metastatic renal cell carcinoma (mRCC). The objectives were to (i) assess the prevalence of proteinuria and hypertension at baseline; (ii) their incidence under anti-VEGF drug treatment; and (iii) evaluate a possible link with overall survival. Methods: Patients from 8 centers were included between 2009 and 2011 with a follow-up of 1 year. They were naïve of any previous anti-VEGF drug treatment and planned to be started on one. The results of the group of patients with mRCC receiving sunitinib are presented. Results: A total of 1, 124 patients were included, among whom 137 had mRCC and 112 received sunitinib. At inclusion, hypertension prevalence was 44%, proteinuria 16%, hematuria 8%, mean modification of diet in renal disease (MDRD) formula 69 mL/min/1.73m2. The incidence of de novo proteinuria and hypertension during follow-up was 75% and 21%, respectively. Among patients with de novo proteinuria, 76% afterwards improved/normalized. Mean MDRD was 72 at the end of follow-up. No thrombotic microangiopathy was reported. Baseline or de novo proteinuria or hypertension were not associated with OS in mRCC patients treated with sunitinib. Conclusions: These results showed that (i) hypertension and proteinuria were frequent at baseline in mRCC patients; (ii) de novo hypertension and proteinuria frequently occur under sunitinib treatment; and (iii) neither hypertension nor proteinuria, either at baseline or de novo, were associated with overall survival in our cohort of "real-life" patients.